Diet and prey availability of terrestrial insectivorous birds prone to extinction in amazonian forest fragments - Mestre,Luiz Augusto Macedo (2010)
This study compared niche breath, prey size, and diet variability in two pairs of sympatric species of terrestrial insectivorous birds, each pair containing one species that can persist in small forest fragments and one that does not. The pairs were Myrmeciza ferruginea and Sclerurus rufigularis; and Formicarius colma and F. analis, respectively. The prey availability in forest fragments was also sampled and compared to the availability in continuous forests. Niche breath indices did not differ between pair members, but diet variability differed in the opposite direction from that hypothesized. Although the two bird species most vulnerable to fragmentation fed on larger prey than less vulnerable species, prey availability, including that based on prey size did not differ among fragmented versus continuous forest sites. Thus, diet per se appeared not to be an important cause of extinction-proneness in these species. The simplest explanation proposed, that vulnerability to fragmentation was directly related to territory size, requires testing. However, it was consistent with observations that the bird species feeding on larger prey also need larger territories.